Glass Delamination in sterile formulations and Drug Recalls: A Review - Kabirdas B Ghorpade; Sharda M Shinde (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2022)
Injectable formulations are constantly facing continuing challenges of glass compatibility. To assure glass compatibility of the injectable formulation in the area of current interest. Most of the common and serious challenges of glass compatibility are glass delamination. Glass delamination is basically the degradation of the glass and formation of the flakes as a result of the incompatibility with the product stored. The other factors which contribute to glass delamination are the Type of glass container used, Storage condition, and Pharmaceutical Processings like terminal sterilization. Glass delamination should be taken very seriously as it is when present in the formulations it is directly related to the health of the patient. This review describes the Factors responsible for the glass delamination and its effect on patient health and the quality control analysis techniques of the same.